T(f+9)=40

Simple and best practice solution for T(f+9)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for T(f+9)=40 equation:


Simplifying
T(f + 9) = 40

Reorder the terms:
T(9 + f) = 40
(9 * T + f * T) = 40
(9T + fT) = 40

Solving
9T + fT = 40

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Reorder the terms:
-40 + 9T + fT = 40 + -40

Combine like terms: 40 + -40 = 0
-40 + 9T + fT = 0

The solution to this equation could not be determined.

See similar equations:

| 5y-7y=10 | | 6x-30=60-3x | | 9r-4=44+6r | | 5(2x+-7)-3(3x-10)+4= | | (D^3-D^2-4D-2)y=0 | | 46+16y=572 | | 4x-39=90 | | -17-20=-13x+80 | | 2x+3=9x+12-x | | 4x+2+6x=82 | | -5d+120=-6d-9 | | 8(3G+5R)= | | 14+29m=28+22m | | -8x-22=-3(x-1) | | 4x+17=90 | | 2f+20=101-f | | 2w-18w=-32 | | 32+12y=420 | | 78=3c+12+-1c+4 | | -139=5x+7+5 | | x-38=84 | | 3m+167=55+4m | | 12y+22=9y | | 3x(x+20)=44 | | -11+8x=-67 | | -2p+28=6p-44 | | -6(x+2)-13=10+1 | | (-10x+35)*(5)=x | | 9t=42 | | 9(-8)-4((-8)-7)= | | -2x+7+7x=-3 | | -65+2x=33-5x |

Equations solver categories